Generalized Composite Numerical Integration Rule Over a Polygon Using Gaussian Quadrature - Hossain, M Alamgir; Islam, Md Shafiqul (Dhaka University Journal of Science, 2015)
The aim of this paper is to evaluate double integrals over a polygon exploiting coordinate transformation. At first any polygon with m-sides is decomposed into (m-2) triangles. Then each triangle is transformed into a standard triangular finite element using the basis functions in local space. Then the standard triangle is decomposed into 4×n2 right isosceles triangles with side lengths 1/n, and thus composite numerical integration is employed. In addition, the affine transformation over each decomposed triangle and the use of linearity property of integrals are applied. Finally, each isosceles triangle is transformed into a 2-sqare finite element to compute new s2 sampling points and corresponding weight coefficients, using s points conventional Gaussian quadrature, which are applied again to evaluate the double integral. We demonstrate some numerical examples through the proposed method. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21956 Dhaka Univ. J. Sci. 62(1): 25-29, 2014 (January)